Circularity in animal production requires a change in the EAT-Lancet diet in Europe - Selm, Benjamin van; Frehner, Anita; Boer, Imke de; Hal, Ollie van; Hijbeek, Renske; Ittersum, Martin K. van; Talsma, Elise F.; Lesschen, Jan Peter; Hendriks, Chantal; Herrero, Mario; Zanten, Hannah van (Springer, 2022)
It is not known whether dietary guidelines proposing a limited intake of animal protein are compatible with the adoption of circular food systems. Using a resource-allocation model, we compared the effects of circularity on the supply of animal-source nutrients in Europe with the nutritional requirements of the EAT-Lancet reference diet. We found the two to be compatible in terms of total animal-source proteins but not specific animal-source foods; in particular, the EAT-Lancet guidelines recommend larger quantities of poultry meat over beef and pork, while a circular food system produces mainly milk, dairy-beef and pork. Compared with the EAT-Lancet reference diet, greenhouse gas emissions were reduced by up to 31% and arable land use reduced by up to 42%. Careful consideration of the feasible substitutability between animal-source foods is needed to define potential roles of animal products in circular human diets.